FAKTOR – FAKTOR YANG MEREFLEKSIKAN SPIRIT INTRAPRENEURSHIP PADA MAHASISWA CORPORATE ENTREPRENEURSHIP UNIVERSITAS CIPUTRA [FACTORS REFLECTING THE INTRAPRENEURSHIP SPIRIT IN CORPORATE ENTREPRENEURSHIP STUDENTS AT CIPUTRA UNIVERSITY] - Yensen Fernando Wijaya; Junko Alessandro Effendy; Metta Padmalia (Universitas Pelita Harapan, 2021)
Corporate entrepreneurship is a course provided by Ciputra University. The purpose of providing corporate entrepreneurship courses is to facilitate students who want to become professionals in a company. In order to become a professional, every study on corporate entrepreneurship aims to instill professional values or what is called Bintang Intrapreneur. The learning undertaken by students during the fourth semester includes ikigai, gallup and undergoing the hack-a-ton program. Learning during the fifth semester is more focused on formulating strategies after graduating from college where you will work, namely by compiling career pyramids and dream companies. This study aims to determine whether the instillation of professional values by corporate entrepreneurship during lectures is actually needed for corporate entrepreneurship students during internships and becomes worthy of being called Intrapreneur Bintang in a company. This research was conducted quantitatively by distributing questionnaires to corporate entrepreneurship students. The researcher uses non-probability purposive sampling as a method to ensure the accuracy of the factors that support the research variables. The results of this study are pro-active variables, opportunity recognition and networking can be reflected by students who have finished taking corporate entrepreneurship courses to become an intrapreneur.Abstrak dalam Bahasa Indonesia: Corporate entrepreneurship merupakan matakuliah yang disediakan oleh Universitas Ciputra. Tujuan disediakan matakuliah corporate entrepreneurship untuk memfasilitasi mahasiswa yang ingin menjadi seorang profesional disebuah perusahaan. Agar bisa menjadi tenaga profesional maka disetiap pembelajaran corporate entrepreneurship bertujuan menanamkan nilai – nilai profesionalitas atau disebut Intrapreneur Bintang. Pembelajaran yang dijalani oleh mahasiswa selama semester empat meliputi ikigai, gallup dan menjalani program hack a ton. Pembelajaran selama semester lima lebih mengarah pada penyusunan strategi setelah lulus kuliah akan bekerja dimana yaitu dengan menyusun piramida karir dan dream company. Penelitian ini bertujuan untuk mengetahui apakah penanaman nilai profesionalitas oleh corporate entrepreneurship selama di perkuliahan, secara nyata dibutuhkan bagi mahasiswa corporate entrepreneurship ketika magang dan menjadi layak disebut Intrapreneur Bintang disebuah perusahaan. Penelitian ini dilakukan secara kuantitatif dengan metode membagi kuisioner kepada para mahasiswa corporate entrepreneurship. Peneliti menggunakan non-probability purposive sampling sebagai metode untuk memastikan ketepatan faktor – faktor yang mendukung variabel penelitian. Hasil dari penelitian ini adalah variabel pro-active, opportunity recognition dan networking mampu direfleksikan oleh mahasiswa yang telah selesai mengambil mata kuliah corporate entrepreneurship untuk menjadi seorang intrapreneur.